Photodegradation Assessment of Calcipotriol in the Presence of UV Absorbers by UHPLC/MSE - Król, Małgorzata; Żmudzki, Paweł; Bucki, Adam; Kryczyk-Poprawa, Agata (Applied sciences, 2025)
Calcipotriol, a synthetic vitamin D3 analogue widely used in psoriasis treatment, requires a detailed stability assessment due to its topical application and potential exposure to UV radiation. As a drug applied directly to the skin, calcipotriol is particularly susceptible to photodegradation, which may affect its therapeutic efficacy and safety profile. The present study focuses on the analysis of calcipotriol photostability. An advanced UHPLC/MSE method was employed for the precise determination of calcipotriol and its degradation products. Particular attention was given to the effects of commonly used organic UV filters—approved for use in cosmetic products in both Europe and the USA (benzophenone-3, dioxybenzone, meradimate, sulisobenzone, homosalate, and avobenzone)—on the stability of calcipotriol. Unexpected degradation of calcipotriol was observed in the presence of sulisobenzone. Importantly, this effect was consistently detected in methanolic solution and in the pharmaceutical formulation containing calcipotriol and betamethasone, which is particularly significant from a practical perspective. This finding underscores the necessity of evaluating photostability under real-life conditions, as cosmetic ingredients, when co-applied with topical drugs on the skin, may substantially influence the stability profile of the pharmaceutical active ingredient. The research resulted in the first-time characterization of four degradation products of calcipotriol. The degradation process was found to primarily affect the E-4-cyclopropyl-4-hydroxy-1-methylbut-2-en-1-yl moiety, causing its isomerization to the Z isomer and the formation of diastereomers with either the R or S configuration. Computational analyses using the OSIRIS Property Explorer indicated that none of the five degradation products exhibit a toxicity effect, whereas molecular docking studies suggested possible binding of two of the five degradation products of calcipotriol with the VDR.